Automated Control System Generation Out of the Virtual Machine. (2016) - Scheifele, Stefan; Verl, Alexander
Abstract: To drastically reduce the commissioning time of a machine tool innovative companies rely more and more on the possibilities of virtual commissioning - commissioning of real controls on virtual machines and plants in order to improve the accuracy and robustness of acting programs. These virtual machines and plants require data defining their behavior and appearance. The mechanical engineering, which is focused on machine modules, uses engineering tools for configuration and parameterization of the needed control systems. These software tools have knowledge of the cross-relationships and dependencies of the individual modules to each other and derive the required data for the control systems (CNC, PLC, …) but also, e.g. the needed documents from a central database. It is desired to generate the required virtual machines and plants automatically and use them for the test of the control systems. In the research project "CassaMobile" a module is understood as a self-sufficient unit, which includes all mechanical and electrical components to fulfil the intended function and either has its own control system or is controlled by a central control system. The difference from engineering by commissioning lists is, that the control system receives a list of all available modules through a query of the physical machine and that the modules are explaining themselves to the control system and not by a central data base. This is made possible by a module-specific configuration memory such as the CIMory (Configuration and Information Memory). An automatic configuration of the control system on the basis of CIMory data has already been presented. This approach does not require a central data base out of which a virtual machine could be generated. However, the commissioning of the control system can be done only after the construction of the actual machine. To overcome this disadvantage, for "CassaMobile" a virtual equivalent was developed: by using the commissioning list, a virtual machine is generated out of virtual modules which is used for virtual commissioning of the control system. The virtual modules can be detected by the control system and have the possibility to explain themselves to the control system like their physical equivalents. The CIMory gets a virtual expression.